Gait patterns in ischemic and hemorrhagic post-stroke patients with delayed access to physiotherapy - Bianca Callegari; Daniela Rosa Garcez; Alex Tadeu Viana da Cruz Júnior; Aline do Socorro Soares Cardoso Almeida; Skarleth Raissa Andrade Candeira; Nathalya Ingrid Cardoso do Nascimento; Ketlin Jaquelline Santana de Castro; Ramon Costa de Lima; Tatiana Generoso Campos Pinho Barroso; Givago da Silva Souza; Anselmo de Athayde Costa e Silva (World Scientific Publishing, 2021)
Objectives: (1) To assess the effects of a conventional, delayed physiotherapy protocol used by Ischemic Stroke (IS) and Hemorrhagic Stroke (HS) post-stroke patients, in their electromyographic activation patterns during hemiparetic gait; and (2) to study whether this protocol may improve the functional abilities in this population. Methods: This is an observational, descriptive, and analytical quasi-experimental trial. Forty patients with unilateral IS (n=25) and HS (n=15) stroke were recruited; the stroke involved the motor cortex or sub-cortical areas, and the patients were able to walk independently. Interventions with standard protocols of physiotherapy were carried out. Evaluations (clinical and gait assessment) were performed at the time of admission and at the end of the protocol. Outcome measures include Stroke Impact Scale, Timed Up and Go Test, and gait electromyographic evaluation. Results: Only IS patients (with an average of 124.4±45.4 months delayed access to physiotherapy rehabilitation) had improvements in Timed Up and Go Test (change in speed=−8.0seg p<0.05) and presented an anticipation of the onset in Upper leg muscles after the intervention. BF (p=0.05), ST (p=0.001), and RF (p=0.024), started their recruitment (onset) earlier at the swing phase of the gait cycle, which is more similar to the normal pattern (grey shadow). IS and HS (120.4±28.4 months since last stroke) patients presented higher electromyographic activation, after physiotherapy, of the posterior leg muscles (gastrocnemius, semitendinosus and biceps femoris) during stance phase (p<0.05). Conclusion: IS patients had improvements after delayed conventional physiotherapy. For HS limited response to intervention was observed.